Question
upstudy study bank question image url

(n) The sum of the first three terms of an arithmetic sequence is 36 and their product is 1140 . Deternine the three terms. (o) A certain sequence has a constant second difference of 8 . The sixth term of the sequence is 172 and the tenth term is 452 . Determine the gencral term. (p) The sum of the first \( n \) terms of a series is given by \( S_{n}=\frac{n}{4}(7-2 n) \). (1) Calculate the sum of the first 30 terms of this series.

Ask by Hammond Reese. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Problem (n):** The three terms are **5, 12, and 19**. **Problem (o):** The general term is \( \mathbf{a_n = 4n^{2} + 6n - 8} \). **Problem (p):** The sum of the first 30 terms is **–795⁄2**.

Solution

Let's address each of your problems one by one: --- ### **Problem (n)** **Given:** - The sum of the first three terms of an arithmetic sequence is 36. - The product of these three terms is 1140. **Objective:** Determine the three terms. **Solution:** 1. **Representation of Terms:** Let the three consecutive terms of the arithmetic sequence be: \[ a, \quad a + d, \quad a + 2d \] where: - \( a \) = first term - \( d \) = common difference 2. **Sum of the Terms:** \[ a + (a + d) + (a + 2d) = 3a + 3d = 36 \\ \Rightarrow a + d = 12 \quad \text{(Equation 1)} \] 3. **Product of the Terms:** \[ a \times (a + d) \times (a + 2d) = 1140 \] Substitute \( d = 12 - a \) from Equation 1: \[ a \times 12 \times (24 - a) = 1140 \\ \Rightarrow a(24 - a) = \frac{1140}{12} = 95 \\ \Rightarrow a^2 - 24a + 95 = 0 \] 4. **Solving the Quadratic Equation:** \[ a = \frac{24 \pm \sqrt{(24)^2 - 4 \times 1 \times 95}}{2} = \frac{24 \pm \sqrt{576 - 380}}{2} = \frac{24 \pm \sqrt{196}}{2} \] \[ a = \frac{24 \pm 14}{2} \] Thus, two possible values for \( a \): - \( a = \frac{38}{2} = 19 \) - \( a = \frac{10}{2} = 5 \) 5. **Determining the Terms:** - **If \( a = 19 \):** \[ d = 12 - 19 = -7 \\ \text{Terms: } 19, \quad 12, \quad 5 \] - **If \( a = 5 \):** \[ d = 12 - 5 = 7 \\ \text{Terms: } 5, \quad 12, \quad 19 \] Both sequences are valid arithmetic sequences with the given sum and product. **Answer:** The three terms are **5, 12, and 19**. --- ### **Problem (o)** **Given:** - A sequence has a constant second difference of 8. - The sixth term (\( a_6 \)) is 172. - The tenth term (\( a_{10} \)) is 452. **Objective:** Determine the general term of the sequence. **Solution:** 1. **Understanding Second Differences:** A constant second difference implies that the sequence is quadratic. The general form of a quadratic sequence is: \[ a_n = An^2 + Bn + C \] The second difference (\( \Delta^2 \)) of a quadratic sequence is \( 2A \). Given \( \Delta^2 = 8 \): \[ 2A = 8 \quad \Rightarrow \quad A = 4 \] So, the general term becomes: \[ a_n = 4n^2 + Bn + C \] 2. **Setting Up Equations:** Use the given terms to create equations: - For \( n = 6 \): \[ 4(6)^2 + B(6) + C = 172 \\ 144 + 6B + C = 172 \\ 6B + C = 28 \quad \text{(Equation 1)} \] - For \( n = 10 \): \[ 4(10)^2 + B(10) + C = 452 \\ 400 + 10B + C = 452 \\ 10B + C = 52 \quad \text{(Equation 2)} \] 3. **Solving the System of Equations:** Subtract Equation 1 from Equation 2: \[ (10B + C) - (6B + C) = 52 - 28 \\ 4B = 24 \\ B = 6 \] Substitute \( B = 6 \) into Equation 1: \[ 6(6) + C = 28 \\ 36 + C = 28 \\ C = -8 \] 4. **Final General Term:** \[ a_n = 4n^2 + 6n - 8 \] **Verification:** - For \( n = 6 \): \[ 4(36) + 6(6) - 8 = 144 + 36 - 8 = 172 \quad \text{(Correct)} \] - For \( n = 10 \): \[ 4(100) + 6(10) - 8 = 400 + 60 - 8 = 452 \quad \text{(Correct)} \] **Answer:** The general term is \( \mathbf{a_n = 4n^{2} + 6n - 8} \). --- ### **Problem (p)** **Given:** - The sum of the first \( n \) terms of a series is: \[ S_n = \frac{n}{4}(7 - 2n) \] - Calculate the sum of the first 30 terms (\( S_{30} \)). **Solution:** 1. **Substitute \( n = 30 \) into the sum formula:** \[ S_{30} = \frac{30}{4}(7 - 2 \times 30) = \frac{30}{4}(7 - 60) = \frac{30}{4}(-53) \] 2. **Simplify the Expression:** \[ S_{30} = \frac{30}{4} \times (-53) = \frac{15}{2} \times (-53) = \frac{-795}{2} = -397.5 \] Alternatively, it can be expressed as a fraction: \[ S_{30} = -\frac{795}{2} \] **Answer:** The sum of the first 30 terms is **–795⁄2** (that is, \( S_{30} = -\frac{795}{2} \)).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find the three terms of the arithmetic sequence, let the terms be \( a - d \), \( a \), and \( a + d \). The sum of these terms is \( (a - d) + a + (a + d) = 3a \). Setting this equal to 36, we get \( 3a = 36 \) which gives \( a = 12 \). The product is given by \( (a - d) \cdot a \cdot (a + d) = 1140 \). Substituting \( a = 12 \), we get \( (12 - d) \cdot 12 \cdot (12 + d) = 1140 \). Simplifying reveals \( 144(d^2 - 72) = 1140 \), leading to \( d^2 = 97.5 \) or \( d \approx 9.87 \). The terms are approximately \( 2.13, 12, 21.87 \). For the sum of the first \( n \) terms of the series given \( S_{n}=\frac{n}{4}(7-2n) \), the sum for \( n = 30 \) is calculated as follows: \[ S_{30} = \frac{30}{4}(7 - 2 \times 30) = \frac{30}{4}(-53) = -397.5 \] So, the sum of the first 30 terms is -397.5. This indicates potentially unusual data, suggesting a careful recheck of original series terms or implications in context!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy